2014
DOI: 10.1021/nn5019945
|View full text |Cite
|
Sign up to set email alerts
|

MoS2/Graphene Cocatalyst for Efficient Photocatalytic H2 Evolution under Visible Light Irradiation

Abstract: Exploiting noble-metal-free cocatalysts is of huge interest for photocatalytic water splitting using solar energy. Here we report a composite material consisting of CdS nanocrystals grown on the suface of a nanosized MoS2/graphene hybrid as a high-performance noble-metal-free photocatalyst for H2 evolution under visible light irradiation. Through the optimizing of each component proportion, the MoS2/G-CdS composite showed the highest photocatalytic H2 production activity when the content of the MoS2/graphene c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
491
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 899 publications
(502 citation statements)
references
References 49 publications
(71 reference statements)
11
491
0
Order By: Relevance
“…15 As an important non-noble cocatalyst, MoS 2 is a highly promising candidate for photocatalysis and many other applications. [16][17][18][19][20] Thus, using MoS 2 is reasonable for strengthening the visible light photocatalytic performance of Bi 2 S 3 . [21][22][23][24] As a cocatalyst, the morphology and nanostructure of MoS 2 , for example, nanoparticles, 25 nanoclusters, 26 nanospheres 27 and nanosheets, 19,28 have considerable effects on the catalytic performance of MoS 2 -activated hybrids.…”
Section: Introductionmentioning
confidence: 95%
“…15 As an important non-noble cocatalyst, MoS 2 is a highly promising candidate for photocatalysis and many other applications. [16][17][18][19][20] Thus, using MoS 2 is reasonable for strengthening the visible light photocatalytic performance of Bi 2 S 3 . [21][22][23][24] As a cocatalyst, the morphology and nanostructure of MoS 2 , for example, nanoparticles, 25 nanoclusters, 26 nanospheres 27 and nanosheets, 19,28 have considerable effects on the catalytic performance of MoS 2 -activated hybrids.…”
Section: Introductionmentioning
confidence: 95%
“…To conquer the drawbacks of wavelength and lifetime limitations, van der Waals heterostructures,15 or lateral heterostructures,16, 17 which are made by stacking a monolayer on the top of another monolayer or a few‐layer crystal or controlled by epitaxial growth of lateral heterojunction, are developed and show great potential for designing high‐performance 2D material‐based photodetectors owing to the combined advantages and synergetic effects of different 2D materials with various band gaps and work functions,18, 19, 20 and the ultrafast layer‐to‐layer transfer speed of carriers 21. To date, various van der Waals heterostructures and lateral heterostructures have been prepared and successfully applied in photodetectors,17, 22 field‐effect transistors,23 photocatalysts,24 and solar cells 16, 25. However, large‐area defect‐free monolayer MoS 2 has not yet been widely demonstrated and accurate transfer and positioning cannot be well achieved, making it difficult to utilize for large‐scale and high‐quality device applications as surface effects, such as surface band bending, surface roughness, photodesorption, gas chemisorption, and surface related defects or states, have significantly important effects on the photoelectric properties of 2D materials 26.…”
Section: Introductionmentioning
confidence: 99%
“…16 The synergetic effects between MoS 2 and graphene have been well demonstrated by using TiO 2 and CdS as prototypes. 17,18 It has been revealed that the electrocatalytic activity of MoS 2 is derived from the undercoordinated sulfur edge sites, while their basal planes remain inert toward hydrogen evolution. 19 For the MoS 2 decorated photocatalysts, their performance can be influenced by many factors, such as morphology, crystalline phase, electronic structure and defect state.…”
Section: Introductionmentioning
confidence: 99%